Digital capabilities and metaverse entrepreneurial performance: Role of entrepreneurial orientation - Shaofeng Wang; Hao Zhang (Journal of Innovation & Knowledge (JIK), 2024)
This study examines the influence of digital capabilities in sculpting entrepreneurial orientation (EO) and enhancing metaverse entrepreneurial performance (MEP). Grounded in the theoretical frameworks of the resource-based view (RBV) and dynamic capability theory (DCT), this research explains the mechanisms through which three facets of digital capabilities (infrastructure, business spanning, and proactive stance) cultivate an ecosystem conducive to entrepreneurial expansion and efficacy within the metaverse. Based on a data set of 403 metaverse entrepreneurs, a multifaceted analytical approach is applied. Partial least squares structural equation modeling (PLS-SEM) is used to assess latent variable relationships. Importance-performance map analysis (IPMA) is used to evaluate the performance and importance of various constructs. Fuzzy-set qualitative comparative analysis (fsQCA) is used to identify complex causal relationships. Collectively, these techniques enable the examination of the interplay among digital capabilities, EO, and MEP. The empirical findings show the positive impact of digital capabilities on EO and MEP, with EO mediating this relationship. These results underscore the need for metaverse entrepreneurs to improve their digital capabilities and EO to achieve enhanced performance within this dynamic entrepreneurial ecosystem.
Keywords: M13; O33; L86; 650; Metaverse; Digital capabilities; Entrepreneurial orientation; Innovation; Knowledge transfer; Entrepreneurial performance